Customs union and Kazakhstan's imports - Asel Isakova; Alexander Plekhanov (Center for Social and Economic Research (CASE), 2012)
The paper provides an empirical analysis of the early impact of formation of the customs union of Belarus, Kazakhstan and Russia and associated changes in imports schedule on the structure of Kazakhstan's imports. Trade creation effects appear to have been insignificant. At the same time the change in tariffs appears to have created some trade diversion, with a significantly negative impact on imports from China in particular and a significantly positive impact on imports from within the customs union. The magnitude this effect is relatively small, however. The results tentatively suggest that the benefits of the new tariff policy per se to Kazakhstan are limited at best. Larger benefits could come from gradual liberalization of services sectors and market access within the economic union.
Keywords: F14; F15; 330; Customs Union; Imports; Exports; Tariffs; Regional Integration; Zollunion; Handelseffekt; Zoll; Zoll; Import; Kasachstan